Provider competence in hypertension management and challenges of the rural primary healthcare system in Sichuan province, China: a study based on standardized clinical vignettes - Yuju Wu; Ruixue Ye; Qingzhi Wang; Chang Sun; Sha Meng; Sean Sylvia; Huan Zhou; Dimitris Friesen; Scott Rozelle (BMC, 2022)
Abstract Background Improving primary care providers' competence is key to detecting and managing hypertension, but evidence to guide this work has been limited, particularly for rural areas. This study aimed to use standardized clinical vignettes to assess the competence of providers and the ability of the primary healthcare system to detect and manage hypertension in rural China. Methods A multi-stage random sampling method was administered to select target health facilities, providers, and households. The clinical vignette script was developed to evaluate provider competence in managing first-visit patients with symptoms of hypertension. Logistic regression was used to explore the factors correlated with provider competence. Provider referral and management rates were combined with patients' facility sorting behaviors to assess the ability of the rural healthcare system to manage hypertension in three policy scenarios. Results A total of 306 providers and 153 facilities were enrolled in our study. In the 306 clinical vignette interactions, 25.9% of providers followed the national guidelines for hypertension consultation. The correct diagnosis was achieved by only 10.1% of providers, and 30.4% of providers were able to prescribe the correct treatment. Multi-variable regression results showed that younger providers (OR = 0.85, 95%CI: 0.73, 0.98) and those who work in township health centers (OR = 4.47, 95%: 1.07, 18.67) were more likely to provide a correct diagnosis. In a free-selection scenario, 29.8% of patients with hypertension were managed correctly throughout the rural system. When all patients first visit village clinics, system-level correct management is reduced to 20.5% but increases to 45.0% when all patients first visit township health centers. Conclusions Rural primary care providers do not have enough competence to detect and treat hypertension cases in China to an acceptable degree. Policy constraints may limit the competence of the rural healthcare system. Research to improve detection and treatment competence in hypertension and optimize health policy is needed.